The suppression of illicit drugs through international law - Boister, Neil (1998)
This study examines the suppression through international law of the illicit production, supply and use of drugs. The study focuses upon the provisions relating to the suppression of illicit drugs in the 1961 Single Convention on Narcotic Drugs, the 1971 Psychotropic Convention, the 1972 Protocol to the Single Convention and the 1988 United Nations Convention Against Illicit Drug Traffic in Narcotic Drugs and Psychotropic Substances. It examines the content of the obligations imposed on states party by these conventions, and gives select examples of how these provisions have been incorporated into domestic law. Chapter one introduces the global drug problem, the policy options available to deal with it, and the regulation of this problem by a system established by international law. Chapter two places the international drug control system in historical context. Chapter three examines the crimes and penalties that the drug conventions require Parties to create in their national law. Chapter four examines the provisions in the drug conventions that deal with jurisdiction over drug offences, extradition of drug offenders, and miscellaneous procedural provisions. Chapter five investigates the international regulation of enforcement in the sense of actual policing, prosecution and punishment of drug offenders. Chapter six examines the alternative methods of control of illicit drug related activities provided for under international law, such as treatment and rehabilitation. Chapter seven examines the supervisory organs of the international drug control system, the supervision of the system and its execution and enforcement. Chapter eight attempts a general comment upon the nature of the system and its aim of suppressing illicit drug use. While the major concern of this study is an examination of the technical rules of international law designed to suppress illicit drugs, it is also concerned with the policy of prohibition that underpins these rules, because of the interrelationship between this policy and the shape of the international legal provisions designed to implement it.